Interaction between Waves and Maritime Structures - Buccino, Mariano; Martinelli, Luca (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is the result of a stimulating Special Issue of Water, focusing on the "Interaction between waves and Maritime Structures". This broadly inclusive title allowed the gathering of articles on different topics of engineering concern, making the book appeal to both scientists and practical engineers. Original contributions on evergreen problems, such as wave overtopping at conventional and unconventional coastal structures, wave-induced pressures at vertical walls, hydraulic stability of rubble mound breakwaters and dynamics of crown-walls indeed represent the main core of the book; however, other intriguing research topics are also tackled, including the solution of the Navier-Stokes equations for biphase flows, the downscaling of large maritime structures in a physical lab, floating bodies mechanics and the numerical modeling of coastline evolution.